Pesticide Exposure Increases The Incidence Of Low Birth Weight (LBW) In Agricultural Areas - Faza, Nadhira; Novita, Reza; Trisnawati, Dian; Kurniyawan, Enggal Hadi; Afandi, Alfid Tri; Kurniawan, Dicky Endrian; Nur, Kholid Rosyidi Muhammad (LPPM Universitas dr. Soebandi, 2025)
Introduction: The involvement of pregnant women in agricultural activities causes pregnant women to be exposed to chemicals contained in pesticides, which will have an impact on the health of pregnant women, especially on reproductive health, which can pose a risk of low birth weight babies. This study aimed to determine the relationship between pesticide exposure and the incidence of low birth weight in agricultural areas. Methods: This research was conducted using the literature review technique; the literature search process used three databases, including Google Scholar, PubMed, and Science Direct, with a publication range from 2020-2024. Results: Pesticide exposure in female farmers influences a determinant of LBW, namely participation in agricultural activities; some articles found that there was no relationship between pesticide exposure and the incidence of LBW; this is because the participation of mothers in agricultural activities is mostly not too long so that the intensity of pesticide exposure in the majority of mothers is still low, in addition, exposure non-organophosphate pesticides had more impact on skin problems in infants rather than low birth weight. Conclusions: Pesticide exposure during pregnancy influences the incidence of LBW; the role of nurses is needed in raising awareness of farmers and their families such as the use of personal protective equipment, managing pesticides according to standards, avoiding direct contact with someone who is bound by pesticides, and storing pesticides out of reach.